2007
DOI: 10.1007/s00432-007-0196-y
|View full text |Cite
|
Sign up to set email alerts
|

Serum level of arginine-vasopressin influences the prognosis of extensive-disease small-cell lung cancer

Abstract: The data from the current study suggested that serum LDH level and PS were the poor prognostic factors for ED-SCLC. But we additionally identified the prognostic significance of serum AVP level, which may be a more useful factor than serum-sodium level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(40 reference statements)
1
3
0
Order By: Relevance
“…However, in line with our results, plasma ADM has been correlated with tumor progression in neuroendocrine carcinomas of various origin [ 40 ]. With regard to copeptin, a surrogate marker for AVP, our findings are consistent with Umemura et al [ 41 ], investigating mature serum AVP in 34 patients with SCLC where increased levels were associated with reduced survival. It is unclear whether AVP is actively involved in carcinogenesis, although an indirect effect on angiogenesis by stimulated secretion of VEGF and endothelin-1 was suggested in vitro [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, in line with our results, plasma ADM has been correlated with tumor progression in neuroendocrine carcinomas of various origin [ 40 ]. With regard to copeptin, a surrogate marker for AVP, our findings are consistent with Umemura et al [ 41 ], investigating mature serum AVP in 34 patients with SCLC where increased levels were associated with reduced survival. It is unclear whether AVP is actively involved in carcinogenesis, although an indirect effect on angiogenesis by stimulated secretion of VEGF and endothelin-1 was suggested in vitro [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 91%
“…In lung cancer, many authors also identified hyponatremia as an independent negative risk factor [30,32,[34][35]. At the same time, Umemura and colleagues found that vasopressin (AVP) is a better prognostic factor than sodium levels [51]. We could confirm that hyponatremia is significantly associated with worse overall survival rates in lung cancer patients.…”
Section: Discussionmentioning
confidence: 60%
“…Most studies of the presence of hyponatremia have been published 15-20 years ago. Some large retrospective studies have shown the presence of hyponatremia to be a negative prognostic factor [2][3][4][5][6], while it was not found to be a statistical significant factor in others [7][8][9][10]. It is possible that some stage migration may have taken place during the period studied and that this may have influenced the results.…”
Section: Discussionmentioning
confidence: 85%